Customized ocular prosthesis: A case report (Indian Journal of Case Reports, 2017)
The eye is a vital organ and an important component of facial expression. Loss of an eye has a crippling effect on the psychology of the patient. Enucleation of the eye is therefore normally followed by fabrication of an ocular prosthesis to improve esthetics. This article describes a technique of rehabilitation of a patient with missing the left eye with custom-made ocular prosthesis.